Contribution to the knowledge on black flies (Diptera: Simuliidae) as vectors of Leucocytozoon (Haemosporida) parasites in Lithuania. (April 2022) - Žiegytė, Rita; Bernotienė, Rasa
Abstract: Black flies (Diptera: Simuliidae) are among the most bothersome blood-sucking dipterans causing severe irritation and distress to poultry, wild birds, animals, and humans globally. These insects are vectors of viruses, bacteria, parasitic protozoans, and nematodes of humans and animals. Parasitic protozoa belonging to Haemosporida (Apicomplexa) are distributed worldwide and black flies are the principal vectors of avian haemosporidian parasites of the genus Leucocytozoon, a common parasite of birds . Based on the detection of parasite DNA in insects, 13 black fly species were reported to be potential vectors of Leucocytozoon in Europe. Information about which species of Simulium can play a role in the transmission of Leucocytozoon parasites is insufficient and needs to be developed. The aim of our study was to determine which black fly species are involved in the transmission of Leucocytozoon parasites in the Eastern Europe. The black fly females were collected in Lithuania using entomological net. They were morphologically identified, dissected to prepare salivary glands preparations, and then screened for the presence of Leucocytozoon parasites using microscopy and PCR-based methods. In all, we collected 437 black fly females belonging to eight species. The DNA of Leucocytozoon (genetic lineage lCOCO18) was detected in one of analysed females identified as Simulium maculatum . All salivary gland preparations were negative for the presence of Leucocytozoon sporozoites. Our results included S. maculatum as a potential vector of Leucocytozoon parasites. Increasing the knowledge on vector ecology, behaviour and improving collection methods may be the key to understand the evolution and diversity of these parasites. Graphical abstract: Unlabelled Image Highlights: Black flies are principal vectors of avian haemosporidian parasites of the genus Leucocytozoon. Black fly females were investigated using both PCR and microscopy of salivary glands. Leucocytozoon DNA (lCOCO18) was detected in Simulium maculatum female. The blood meal source of four Simulium maculatum females contained human DNA.